Guía para buscar libros en el catálogo de la Biblioteca de FOD, UANL - Muela Meza, Zapopan Martín (Universidad Autónoma de Nuevo León, 2011)
Guía para buscar libros en el catálogo de la Biblioteca de FOD, UANL